Activating social strategies: Face-to-face interaction in technology-mediated citizen science. (1st November 2016) - Cappa, Francesco; Laut, Jeffrey; Nov, Oded; Giustiniano, Luca; Porfiri, Maurizio
Abstract: The use of crowds in research activities by public and private organizations is growing under different forms. Citizen science is a popular means of engaging the general public in research activities led by professional scientists. By involving a large number of amateur scientists, citizen science enables distributed data collection and analysis on a scale that would be otherwise difficult and costly to achieve. While advancements in information technology in the past few decades have fostered the growth of citizen science through online participation, several projects continue to fail due to limited participation. Such web-based projects may isolate the citizen scientists from the researchers. By adopting the perspective of social strategy, we investigate within a measure-manipulate-measure experiment if motivations to participate in a citizen science project can be positively influenced by a face-to-face interaction with the scientists leading the project. Such an interaction provides the participants with the possibility of asking questions on the spot and obtaining a detailed explanation of the citizen science project, its scientific merit, and environmental relevance. Social and cultural factors that moderate the effect brought about by face-to-face interactions on the motivations are also dissected and analyzed. Our findings provide an exploratory insight into a means for motivating crowds to participate in online environmental monitoring projects, also offering possible selection criteria of target audience. Graphical abstract: Highlights: We investigate face-to-face interaction to boost participation in crowd projects. Interactions are empirically studied in an environmental citizen science project. Contributor motivations are collected in a measure-manipulate-measure experiment. We offer empirical evidence of increase in participants' motivation. Social and cultural factors are analyzed to apprehend the target audience.